2007
DOI: 10.1016/j.schres.2007.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Differential alterations of kainate receptor subunits in inhibitory interneurons in the anterior cingulate cortex in schizophrenia and bipolar disorder

Abstract: The aim of this study was to examine whether glutamatergic inputs onto GABA interneurons via the kainate receptor in the anterior cingulate cortex may be altered in schizophrenia and bipolar disorder. Hence, in a cohort of 60 post-mortem human brains from schizophrenia, bipolar disorder, and normal control subjects, we simultaneously labeled the mRNA for the GluR5 or GluR6 subunit of the kainate receptor with [(35)S] and the mRNA for the 67 kD isoform of the GABA synthesizing enzyme glutamic acid decarboxylase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 70 publications
2
44
0
Order By: Relevance
“…Consistent with our hypothesis, we observed lower ACC GABA in patients with manic or mixed episodes when compared with TD. Overall, our findings are in agreement with studies implicating the GABAergic neurotransmitter system (Schousboe 2003;Bak et al 2006;Wang et al 2006;Bhagwagar et al 2007;Woo et al 2007;Brady et al 2013) in the pathophysiology of BD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our hypothesis, we observed lower ACC GABA in patients with manic or mixed episodes when compared with TD. Overall, our findings are in agreement with studies implicating the GABAergic neurotransmitter system (Schousboe 2003;Bak et al 2006;Wang et al 2006;Bhagwagar et al 2007;Woo et al 2007;Brady et al 2013) in the pathophysiology of BD.…”
Section: Discussionsupporting
confidence: 92%
“…Abnormalities within the c-aminobutyric acid (GABA)ergic neurotransmitter system have also been implicated in the pathophysiology of BD through GABA receptor gene polymorphisms (Benes and Berretta 2001;Massat et al 2002;Otani et al 2005), postmortem (Benes and Berretta 2001;Knable et al 2004;Torrey et al 2005;Woo et al 2007) and MRS studies (Wang et al 2006;Bhagwagar et al 2007;Brady et al 2013). Specifically, irregularities in ACC GABA have been shown in patients with BD (Bhagwagar et al 2007;Woo et al 2007;Brady et al 2013). The changes in excitatory (i.e., glutamatergic) and inhibitory (i.e., GABAergic) neurotransmission may be synergistic: Glial produced glutamine is the source for both neuronal glutamate and GABA.…”
Section: Introductionmentioning
confidence: 99%
“…However, because only ∼10% of all CB mRNA-containing cells express NR2A mRNA, conceivably small changes in the magnitude of mRNA expression would not be detectable by in situ hybridization (Woo et al, 2008b). In an independent sample, the density of GAD 67 -containing GABAergic neurons that express the GluR5 subunit of the kainate receptor was found to be decreased by ∼40% in layer II of the pgACC in BD and schizophrenia (Woo et al, 2007). No change in mRNA expression was observed in GluR6-containing neurons; the GluR6 receptor is expressed predominantly on pyramidal cells.…”
Section: Resultsmentioning
confidence: 96%
“…It has been suggested that this region shows a particular vulnerability in schizophrenia 17 possibly owing to altered basolateral amygdala projections to CA2/3. 17,[76][77][78][79] The CA2/3 region has close functional connections to many other brain regions including the hypothalamus, septal nucleus, 80 subiculum, 81 and the CA1 region of the hippocampus. 82 Thus, while we confirm and extend the knowledge implicating the hippocampus and the CA2/3 region in schizophrenia 20,83 and bipolar disorder, changes in this region will have widespread consequences within the brain.…”
Section: Commentmentioning
confidence: 99%